Species and site characteristics that permit the association of fast-growing trees with crops: The case of Eucalyptus deglupta as coffee shade in Costa Rica - Schaller, Michaela; Schroth, G?otz; Beer, John W.; Jiménez, Francisco (Forest Ecology and Management, 2003)
The benefits that tropical farmers derive from associating trees with crops may be reduced or outweighed by competition for light and soil resources, and the use of incompetitive trees in agroforestry associations is therefore a standard recommendation. However, under certain conditions tropical farmers use very fast-growing and presumably competitive trees in tree-crop associations. We studied the factors which allow the use of Eucalyptus deglupta as coffee shade in parts of Costa Rica, considering three possible explanations: (a) the availability of soil resources matches the requirements of the two species so that competition cannot arise; (b) complementary resource use reduces competition; and (c) coffee plants possess sufficiently competitive root systems to cope with the competition of fast-growing trees. We measured coffee and tree growth, soil nutrient availability, root distribution and dynamics of 4- to 5-year-old coffee and E. deglupta shade trees on a private coffee farm with recommended fertilization in a high-rainfall area in Costa Rica. There was no evidence of a negative effect of the trees on coffee growth, yields and mineral nutrition despite fast tree growth. However, a significant small-scale partitioning of the soil space between the root systems, with most of the coffee roots close to the coffee rows and most of the tree roots in the interrow spaces, was evidence for root interactions between the two species, resulting in complementary use of soil resources. Apparently, the root system of coffee was sufficiently competitive to restrict the rooting space of the trees. Trees and coffee also differed in the depth distribution of their roots, with the trees having the shallower root systems. The compatibility of coffee with fast-growing shade trees at this and similar sites can be explained with a combination of all three hypothesized mechanisms. © 2002 Elsevier Science B.V. All rights reserved.
Keywords: Biodiversity; Crops; Rain; Soils; Coffee Shades; Forestry; Agroforestry; Coffee; Competition (ecology); Root System; Shading; Tropical Region; Farm Crops; Forestry; Rain; Soil; Costa Rica; Coffea; Coffea Arabica; Eucalyptus; Eucalyptus Deglupta